ANALYSIS PERCEPTION FARMER ONION RED TO SHALLOT DEVELOPMENT PROGRAM IN DELI SERDANG REGENCY - Fuad Balatif; Dian Dhika; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The purpose of this study was to analyze shallot farmers' perceptions of the shallot development program. The research method used was a survey, which involved interviews and direct observation or supervision at the broad development locations. Interview guidance and data collection were guided by a structured questionnaire. The sampling technique for locations/regions was purposive based on the potential and carrying capacity of the commodity's development. Respondents were drawn using a purposive cluster sampling method to group the sample according to the research objectives. A total of 100 individuals were selected from farmer groups involved in shallot production. The analysis technique used was descriptive research. The results showed that farmers' perceptions categorized as high were those for community support/involvement (114.10%), assistance with inputs (123.47%), and assistance with seeds (101.10%). This means that the average perception of shallot farmers in Deli Serdang Regency for these criteria exceeded 100%. The farmer perception criteria that fell into the low category were program clarity (93.27%), program targeting accuracy (89.74%), mentoring and extension (86.81%), and financial assistance (91.49%). This criterion is considered low because the average percentage of this criterion is less than 100%.